2006
DOI: 10.1103/physreva.74.031601
|View full text |Cite
|
Sign up to set email alerts
|

Bose-Einstein-condensate interferometer with macroscopic arm separation

Abstract: A Michelson interferometer using Bose-Einstein condensates is demonstrated with coherence times of up to 44 ms and arm separations up to 180 m. This arm separation is larger than that observed for any previous atom interferometer. The device uses atoms weakly confined in a magnetic guide and the atomic motion is controlled using Bragg interactions with an off-resonant standing-wave laser beam.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 28 publications
2
97
0
Order By: Relevance
“…More recent experiments using Bose condensates [8] have shown that the external state coherence can be preserved for approximately 200 ms, where the decoherence is dominated by atom-atom interactions. Interferometry experiments using either condensed atoms in a weak trap or noncondensate atoms in a waveguide with precise angular alignments have been shown to have phase-stable interrogation times of ≈50 ms, where the dephasing is induced by inhomogeneities in the confining potential [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…More recent experiments using Bose condensates [8] have shown that the external state coherence can be preserved for approximately 200 ms, where the decoherence is dominated by atom-atom interactions. Interferometry experiments using either condensed atoms in a weak trap or noncondensate atoms in a waveguide with precise angular alignments have been shown to have phase-stable interrogation times of ≈50 ms, where the dephasing is induced by inhomogeneities in the confining potential [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…If the gas is cooled below the recoil temperature and is split using a laser pulse, a large relative separation between each arm of the interferometer can be achieved [6]. By exposing the atoms in each arm to a different environment, precision measurements of localized phenomena can be performed.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have built trapped atom interferometers using atomic gases that are both above and below the recoil temperature [4,5,6,7,8,9]. To date, all interferomters that use gases below the recoil temperature have utilized atoms in a nearly pure Bose-Einstein condensate (BEC).…”
Section: Introductionmentioning
confidence: 99%
“…Seminal examples of atom interferometry followed soon after the first BEC was produced [33,34], including Ketterle's two-condensate experiment, followed more recently by a compact realisation on an atom chip [35]. Large-area interferometers with BEC have also been realised [36], with atom interferometer sensitivities to phase shifts scaling linearly with the enclosed area.…”
Section: Bose-condensed Gasesmentioning
confidence: 99%